Decision-Making of Older Patients in Context of the Doctor-Patient Relationship: A Typology Ranging from "Self-Determined" to "Doctor-Trusting" Patients. (18th April 2013) - Wrede-Sach, Jennifer; Voigt, Isabel; Diederichs-Egidi, Heike; Hummers-Pradier, Eva; Dierks, Marie-Luise; Junius-Walker, Ulrike
Abstract : Background . This qualitative study aims to gain insight into the perceptions and experiences of older patients with regard to sharing health care decisions with their general practitioners. Patients and Methods . Thirty-four general practice patients (≥70 years) were asked about their preferences and experiences concerning shared decision making with their doctors using qualitative semistructured interviews. All interviews were analysed according to principles of content analysis. The resulting categories were then arranged into a classification grid to develop a typology of preferences for participating in decision-making processes. Results . Older patients generally preferred to make decisions concerning everyday life rather than medical decisions, which they preferred to leave to their doctors. We characterised eight different patient types based on four interdependent positions (self-determination, adherence, information seeking, and trust). Experiences of a good doctor-patient relationship were associated with trust, reliance on the doctor for information and decision making, and adherence. Conclusion . Owing to the varied patient decision-making types, it is not easy for doctors to anticipate the desired level of patient involvement. However, the decision matter and the self-determination of patients provide good starting points in preparing the ground for shared decision making. A good relationship with the doctor facilitates satisfying decision-making experiences.